Copper phytotoxicity in agricultural crops cultivated in tropical soils - Engelhardt, Mateus Moreira; Lima, Francielle Roberta Dias de; Martins, Gabriel Caixeta; Vasques, Isabela Cristina Filardi; Silva, Aline Oliveira; Oliveira, Jakeline Rosa; Reis, Rayner Hugo Cassa Louzada; Guilherme, Luiz Roberto Guimarães; Marques, João José Granate de Sá e Melo (Semina: Ciências Agrárias, 2020)
Copper is a micronutrient for living organisms, but at high concentrations it may cause several deleterious effects. The objective of this study was to evaluate the behavior of agricultural crops to different concentrations of Cu in the soil. The species Triticum aestivum (wheat), Zea mays (maize), Oryza sativa (rice), Phaseolus vulgaris (dry bean), Glycine max (soybean), and Raphanus sativus (radish) were cultivated in the soils Typic Hapludox (TyHpx) and Rhodic Acrudox (RhAcx). The experiment was carried out in a greenhouse and the soils were set in pots in a completely randomized design, with four replicates per treatment adding the following Cu concentrations (as Cu-nitrate): 0, 75, 150, 300, 600, 800, 1000, 1200 mg kg-1 dry soil. Measurements of biological variables, such as shoot dry weight (SDW), plant height, stem diameter, and number of leaves were carried out, in addition to determining Cu content in the SDW. At the TyHpx, a decreasing order of tolerance to Cu phytotoxicity was: dry bean, maize, soybean, wheat, radish, and rice. However, at the RhAcx, the decreasing order was: maize, soybean, radish, wheat, dry bean, and rice. The species that revealed the highest sensitivity to high Cu concentrations in soil was rice and that with the lowest sensitivity was maize.